Sleep duration and tiredness at school from childhood to adolescence: repeated surveys over 10 years in Swedish schoolchildren - Pernilla Garmy (Journal of Research in Nursing, 2026)
Background: This study aimed to examine insufficient sleep across ages 6–16 years and to determine whether short sleep was associated with tiredness at school. Methods: A repeated survey design was used, with data collected at four time points over a 10-year period in a municipality in southern Sweden. Participants were assessed at ages 6–7 ( n = 560), 10 ( n = 1253), 14 ( n = 1067) and 16 years ( n = 1449). Sleep duration on school days and tiredness at school were analysed using descriptive and inferential statistics. Results: The prevalence of insufficient sleep was below 10% among children aged 6–10 years, 31% among 14-year-olds and 74% among 16-year-olds. The prevalence of often or always feeling tired at school was 3% among children aged 6–7 years, 10% among children aged 10 years, 40% among 14-year-olds and 73% among 16-year-olds. Shorter sleep was associated with increased tiredness at school ( p < 0.05). Conclusion: Although sleep duration declines from childhood to adolescence as expected, an increasing proportion of adolescents report tiredness at school and do not meet recommended sleep-duration guidelines. These findings highlight the need for early and sustained nursing and school-based interventions to promote healthy sleep habits.